Growth or stagnation? : a review of Bangladesh's development, 1996 - Centre for Policy Dialogue (Bangladesh) (Dhaka : University Press, 1997)
Contributed articles.
Includes bibliographical references.
Keywords: Rural poor -- Bangladesh; Bangladesh -- Economic policy; Bangladesh -- Economic conditions